2022
DOI: 10.3390/molecules27072192
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Nanoparticle Formulation of Diallyl Trisulfide Chemosensitizes the Growth Inhibitory Activity of Doxorubicin in Colorectal Cancer Model: A Novel In Vitro, In Vivo and In Silico Analysis

Abstract: Garlic’s main bioactive organosulfur component, diallyl trisulfide (DATS), has been widely investigated in cancer models. However, DATS is not suitable for clinical use due to its low solubility. The current study seeks to improve DATS bioavailability and assess its chemopreventive and chemosensitizing properties in an AOM-induced colorectal cancer model. The polyethylene glycol coated Distearoylphosphatidylcholine/Cholesterol (DSPC/Chol) comprising DATS-loaded DATSL and doxorubicin (DOXO)-encapsulated DOXL li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The ABW from each group was recorded from week 0 and continuously monitored every 2 weeks for 22 weeks. The RLW was estimated using the formula below after sacrificing the animals from all groups, as described earlier [ 49 ]. The ABWs of the mice from each group were recorded every two weeks throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…The ABW from each group was recorded from week 0 and continuously monitored every 2 weeks for 22 weeks. The RLW was estimated using the formula below after sacrificing the animals from all groups, as described earlier [ 49 ]. The ABWs of the mice from each group were recorded every two weeks throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, molecular docking analysis identified potential interactions with cancer-related proteins, such as MMP-9, suggesting a mechanism for DATS action. This study presents a promising approach for colorectal cancer prevention and treatment, highlighting the potential of DATSL and DOXL as a novel and efficient therapeutic strategy [72].…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…The unique attributes of lipid-based nanoparticles, encompassing their biocompatibility, stability, and capacity to carry imaging payloads, render them well-suited for the precise and noninvasive diagnosis of CRC [71]. For instance, Alrumaihi et al [72] aimed to enhance the bioavailability of diallyl trisulfide (DATS), a bioactive compound with known anticancer properties, by encapsulating it in polyethylene glycol-coated liposomes (DATSL) and combining it with doxorubicin (DOXO)-encapsulated liposomes (DOXL). DATSL and DOXL exhibited significant sensitivity in inhibiting colon cancer cell proliferation, both individually and in combination, with a synergistic effect observed at specific concentration combinations, lowering the IC50 doses of DATS and DOXO by over 8-and 14-fold, respectively.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…DATS has also been demonstrated to be effective as a chemopreventive agent against CRC. One study found that DATS treatment at a concentration of 25 mg/kg body weight, three times per week via an unspecified route, significantly reduced tumor number and incidence in an AOM-induced CRC mouse model ( Table 1 ) [ 23 ]. Much like DADS, DATS is also hydrophobic and exhibits low bioavailability, limiting its potential for clinical use.…”
Section: Organosulfur Compounds Derived From Allium ...mentioning
confidence: 99%
“…Another family of plant nutraceuticals are organosulfur compounds, such as diallyl trisulfide (DATS), methylsulfonylmethane, and isothiocyanates. They have been tested as antitumor or chemosensitizers in the co-therapy of CRC, due to their inhibition of matrix metalloproteases, inhibition of carcinogen activation enzymes, and induction of apoptosis [ 23 , 24 , 25 ]. In the human diet, these organosulfur compounds are present in vegetables such as garlic, onion, broccoli, cabbage, and others from those plant families ( Amaryllidaceae , Brassicaceae ) [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%